A Criminological Study Of The Impact Of Murder On The Community And Online Motorcycle Ticket Drivers - Tika Hairani; Syahranuddin Syahranuddin; Chairuni Nasution (Fakultas Hukum Dehasen, 2026)
This study examines how robbery crimes impact society and online motorcycle taxi drivers in Indonesia from a criminological perspective. The increase in street crime, particularly robbery, indicates a lack of legal protection for informal sector workers who work in public environments. This study uses normative law, employing a legislative and conceptual approach. The results of the study show that regulations protecting online motorcycle taxi drivers do not fully ensure their safety at work. Robbery causes material losses, emotional trauma, and a sense of insecurity in the community. From a criminological perspective, economic pressure, social inequality, and a lack of social bonds are the main causes of robbery. To prevent similar cases from recurring, the government and law enforcement agencies must strengthen law enforcement, improve social protection, and increase surveillance in crime-prone areas.